2005
DOI: 10.1097/01.aids.0000180790.77379.3a
|View full text |Cite
|
Sign up to set email alerts
|

Potential hazard of pharmacokinetic interactions between lopinavir–ritonavir protease inhibitors and irinotecan

Abstract: The IHDS may be a useful screening test to identify individuals at risk for HIV dementia in both the industrialized world and the developing world. Full neuropsychological testing should then be performed to confirm a diagnosis of HIV dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
191
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 229 publications
(199 citation statements)
references
References 6 publications
7
191
1
Order By: Relevance
“…Furthermore, item convergence between the IHDS and neuropsychological domains was non-significant, indicating that the IHDS does not adequately tap into the neuropsychological constructs sensitive to HAND. One possible factor for this may stem from the reality that the IHDS was developed to assess HAD rather than more mild forms of HAND, like ANI or MND (Sacktor et al, 2005). However, it should also be noted that the IHDS did have an overall trend with the domains, suggesting that there may be a convergence between the variables, albeit a convergence that was weaker than that observed with the HDS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, item convergence between the IHDS and neuropsychological domains was non-significant, indicating that the IHDS does not adequately tap into the neuropsychological constructs sensitive to HAND. One possible factor for this may stem from the reality that the IHDS was developed to assess HAD rather than more mild forms of HAND, like ANI or MND (Sacktor et al, 2005). However, it should also be noted that the IHDS did have an overall trend with the domains, suggesting that there may be a convergence between the variables, albeit a convergence that was weaker than that observed with the HDS.…”
Section: Discussionmentioning
confidence: 99%
“…It is comprised of three items: Finger Tapping (motor speed), an alternating hand sequence item (psychomotor speed), and a four-word verbal memory item. The highest possible score on the IHDS is 12, with a cutoff of 10 or below indicative of risk for dementia (Sacktor et al, 2005). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Antoniou et al [14] reported that the concomitant use of HAART and in particular the inclusion of PI (like in our patient) associated with cancer chemotherapy, may augment the risk of haematological and gastrointestinal toxicity secondary to pharmacodynamic drug interactions. Moreover, simultaneous CPT-11 and PI should be administered with extreme caution and very close monitoring due to their interaction [15]. In fact, Corona et al [15] demonstrated that the concomitant use of PI and irinotecan could be the cause of a persistent grade G2 WHO neutropenia due to interference with the common metabolic pathway (P450).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, simultaneous CPT-11 and PI should be administered with extreme caution and very close monitoring due to their interaction [15]. In fact, Corona et al [15] demonstrated that the concomitant use of PI and irinotecan could be the cause of a persistent grade G2 WHO neutropenia due to interference with the common metabolic pathway (P450). In our case, the concomitant use of CPT-11 and PI did not cause any severe toxicity.…”
Section: Discussionmentioning
confidence: 99%